Ambiente térmico e desempenho de leitões até a desmama alimentados com dieta suplementada com óleo de coco - Deminicis, Renata Gomes da Silveira (2015)
Among the oils used for animal energy supplementation, coconut oil has been shown to be superior in weight gain and improved feed conversion. By having greater amount of medium-chain fatty acids makes has a different metabolic behavior by virtue of its structural characteristics, permitting high absorption in the intestine. The objective of this study was to perform environmental characterization, evaluate performance and mortality birth weaning piglets undergoing diet supplemented with coconut oil. The experiment was carried out using pig maternity facilities in White Clay Farm in the town of Canaan, located in the Zona da Mata, southeastern Minas Gerais. It is testing the use of coconut oil supplementation in suckling piglets from birth to weaning was done. 120 animals were distributed in a completely randomized design, with two treatments (supplementation with oil and without supplementation) with four replications (matrices) and 12 piglets each. The shelters provided stable conditions in the hottest hours of the day, over the stalls. The relative humidity remained below ideal levels for pigs at the hottest times of the day; BGT was appropriate on the recommendation of thermal comfort. It was found that there was no effect ( p> 0.05 ) of supplementation with coconut oil use over the average daily weight gain (g / day) of piglets until weaning , the obtained values were 227 g / day and 228 g/day , without the use and the use of coconut oil , however the mortality rate of the piglets was supplemented by 1.66 % for those who received no supplementation it was 5%, showing the importance of coconut oil when taking into consideration the production of piglets per sow .